Investors' intention to use mobile investment: an extended mobile technology acceptance model with personal factors and perceived reputation - Pick-Soon Ling; Kelvin Yong Ming Lee; Liing-Sing Ling; Mohd Kamarul Anwar Mohd Suhaimi (Cogent Business & Management, 2024)
Mobile investment has been introduced with technological advancements and the enhancement of mobile device functions. However, relatively limited studies have been particularly focused on the determinants of adoption intention on mobile investment. Therefore, this study aimed at exploring the factors affecting investment intention (INT) to use mobile investment by considering the influence of personal factors (mobile self-efficacy [MSE], mobile innovativeness [MI], and attitudes [ATT]), and perceived reputation (PR) through an extended mobile technology acceptance model (MTAM). Purposive sampling was utilised to obtain 213 completed responses, which were then analysed using the partial least squares structural equation modelling (PLS-SEM), and the importance-performance map analysis (IPMA). The results showed that mobile usefulness (MU), MI, PR, and ATT substantially affect INT usage, while MSE had no significant effect on INT usage. Additionally, both MSE and PR significantly influenced ATT, but MI had an insignificant influence on ATT. This study disclosed the missing information by identifying the critical factors of mobile investment adoption using a novel framework developed from the perspective of personal factors and platform providers' PR. Furthermore, the study provided some significant practical implications, as the findings could be referred to by the stakeholders in formulating policies and strategies to stimulate consumers to adopt mobile investment as their investment platform.
Keywords: 650; Mobile investment; mobile technology acceptance model; mobile technology; perceived reputation